DUKUNGAN KELUARGA DENGAN KEPATUHAN MINUMOBAT PASIEN TUBERKULOSIS DI PUSKESMASMANGANITU KABUPATEN SANGIHE - Yonatan Tahulending; Vivi Mampuk; Adi Yeremia Mamahit (Yayasan Syalom Cipta Sumikolah, 2024)
It is estimated that about one-third of the world's population has been infected by Mycobacterium Tuberculosis. Tuberculosis in Indonesia is a health problem that must be addressed by the government. The purpose of this study was to determine the Relationship between Family Support and Compliance in Taking Tuberculosis Patients' Medication. This study is descriptive analytical using a cross-sectional study approach, where in this design both variables are measured at the same time with 30 samples. Based on the Fisher exact test, the p value in this study is 0.039 or less than the a value (0.05), which means Ho is rejected. The conclusion of this study is that most families of patients undergoing tuberculosis treatment support patients in carrying out treatment, most patients with tuberculosis are compliant in undergoing treatment. There is a significant relationship between family support and compliance in taking tuberculosis patients' medication at the Manganitu Health Center, Sangihe Regency.